Plaque Control in Patients with Orthodontic Appliances - Al-hankawe, Firas Ahmed Saadallah; Nanobashvili, Ketevan (Caucasus Journal of Health Sciences and Public Health, 2016)
Braces are used to move teeth into the ideal position and align occlusion. Malocclusion is used to describe the misalignment of teeth between the upper and lower dental arches, using the first molars as a reference point. Orthodontic anomalies and malocclusion are not recognized by bio archeologists. Malocclusion now generally occurs in much of the population, but skeletal remains show that malocclusion was relatively unusual before the 19th and 20th centuries. The goal of braces is a beautiful smile and a good bite. Many people find a beautiful smile adds to self-esteem, self-confidence and leads toward career advancement. Used to move teeth into the ideal position and align how they bite together, known as occlusion. We make braces when we have (Breathing or swallowing problems, malocclusion, disfiguring of the face & mouth, Missing or extra teeth, Self-image, Spacing between teeth, Speech, chewing or biting problems. Risk factors related to braces: age – because of teenagers are affected mostly to orthodontic treatment, many complications may be connected to this age group: behavior – none loving of tooth brushing and hormonal changes, which helps to occur gum inflammation. Changes related to dentogingival plaque accumulation. Tooth malalignment – due orthodontic treatment self cleaning and usual plaque control is limited. And with dislocated teeth these problems may get worst. The side effect of braces: Resorption of root, Discomfort in mouth, Oral Hygiene, Gum Disease and Tooth Decay/Stains, Injuries from Appliances may be it is happening because the wire of the braces, Loose or Poor Quality Fillings, Crowns or Bridges, Jaw Joint Clicking and/or Pain. Basic brushing techniques, is an important part of your dental care routine. For a healthy mouth and smile the American Dental Academy recommends you: Brush your teeth twice a day with a soft-bristled brush. The size and shape of your brush should fit your mouth allowing you to reach all areas easily. Replace your toothbrush every three or four months or sooner if the bristles are frayed. A worn toothbrush won’t do a good job of cleaning your teeth. Make sure to use an American Dental Academy – accepted fluoride toothpaste. Flossing: we use the flossing for the interproximal area between the teeth. We use it like c-shape around each teeth. Moved in a cervical occlusion direction. Special tool for braces to get better access between and around the brackets of the appliance. Chemotherapeutical mouthwashes are also needed for orthodontic patients. Because of high plaque accumulation risk, doctors often administrate bactericidal solutions for this purpose. Mostly the active component of these solutions is chlorhexidine, or even some antiseptic solutions such – H2O2 (Hydrogen peroxidase) or Iodine.